EVALUASI IMPLEMENTASI KEBIJAKAN PROGRAM WAJIB BELAJAR 12 TAHUN DI KOTA DEPOK JAWA BARAT - Elyasa Elyasa (Jurnal Manajemen Pendidikan, 2016)
This study aims to determine how the implementation of the policy of compulsory education to twelve years in the city of Depok, West Java (Case Study On Education Level Senior High School). This study is a qualitative study using a Discrepancy Evaluation Model (DEM). This research was conducted in the scope of Depok City Department of Education in 2015 until 2016, data were collected through interviews, observation and documents. Data were analyzed with descriptive qualitative. Components of the evaluation in this study, among others; evaluation of all aspects of planning, evaluation aspects of the implementation,and evaluation results. The result showed that the policy of compulsory education to twelve years in the city of Depok positive impact, because it is able to suppress the school dropout (APS) rate to 0.1%, and increase the participation and coarse (APK) 65,86% and the net enrollment (APM) rate of 37,57%.